Enactors or reactors? Work-life border management for women in law in Nigeria - Beauregard, T. Alexandra; Adisa, Toyin Ajibade (Community, Work and Family, 2021)
Work-family border theory casts individuals as protagonists who are enactive rather than reactive in shaping borders between work and personal life domains. To what extent is this the case in strongly patriarchal contexts that constrain women’s personal agency? This qualitative study conducted with 32 female lawyers, magistrates and justices in Nigeria shows how participants engage in new border management tactics in response to context-specific institutional and social factors. Faced with public harassment and physical assault in a country where violence against women is normalised, female legal professionals restructure family borders to extend no further than their homes and retain police attachés as border-keepers. When their families are reconfigured via nonconsensual polygamous marriages, women’s work borders are strengthened by co-wives performing domestic labour and family borders are strengthened by co-wives’ assistance with job tasks, thereby reducing participants’ work-family conflict. Rather than strategically enacting work-life borders within known situational constraints, Nigerian female legal professionals react to involuntary events that limit their agency to negotiate desired work and personal lives. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; famille; intersectionnalité; maternité; nigeria; patriarcat; polygamie; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail